Location of appropriate areas for artificial feeding of shahriar plain with improvement of groundwater condition approach by Using Boolean logic model - parviz kardavani; Farideh Asadian; mohammad reza Fallah (تحقیقات کاربردی علوم جغرافیایی)
The irregular exploitation of groundwater aquifers in Shahriyar Plain has caused the drop of ground-water level in the region. Artificial nourishment of aquifers can increase the size of ground-water storage, reduce its level drop, and also prevent the advance of brine and drying of the aqueducts. In this study, we tried to integrate GIS and Boolean logic in order to identify the best areas for artificial recharge in Shahriar Plain. So, the seven factors (slope, permeability, thickness of alluvium, portability, both drop zones, land use and electrical conductivity) of water samples were specified in GIS and then respective maps were prepared. Then, using the acquired weight of each layer, maps for each weighted factors of locating were integrated. Using Boolean logic, final maps were prepared in two classes: suitable and unsuitable. Finally, the best place for the implementation of artificial recharge of aquifers in the region was identified. Results indicated that the suitable regions mostly lie in areas with slopes less than 3 % and that they are mostly near Chitgar river.